New Research Facility: A Note on the Russian Military Studies Archive - Daniels, Rachel J.; Main, Steven J. (Taylor & Francis, 2016)
The Russian Military Studies Archive (RMSA) was formally launched in November 2015. Managed by Cranfield University’s Barrington Library on behalf of the Defence Academy, the RMSA is a new research facility based at the Defence Academy of the United Kingdom in Shrivenham, Wiltshire.
Keywords: 43 History, Heritage and Archaeology; 44 Human Society; 4303 Historical studies; 4408 Political science